How can multi-professional education support better stewardship? - Pereira,N; Castro,Sanchez EM; Nathwani,D (Infectious Disease Reports, 2017)
Antimicrobial stewardship is widely accepted as an efficient strategy to combat the growing threat of antimicrobial resistance. Education is one of the cornerstones of successful antimicrobial stewardship programs. There is also general agreement that antimicrobial stewardship is a team effort that must involve the whole continuum of healthcare workers. Providing adequate education for all different professionals although challenging is deemed crucial to achieve good results. This paper reviews the different strategies available to educate the multiple healthcare workers, discusses how education can improve antimicrobial stewardship programs and outlines some of the challenges faced and research gaps that need to be addressed in order to improve education in this field.